Formation and development perspectives of eco-pharma - Kotvitska, A. A.; Tsubanova, N. A.; Kononenko, N. M.; Ostapets, M. O. (Journal of Education, Health and Sport, 2019)
The aim of our research is to analyze the impact of pharmacy on human ecology and environment, to generalize and structure the identified interactions and interrelations. We are using methods of scientific analysis such as generalization, comparison, content analysis. The main components and development perspectives of a new interdisciplinary direction, namely eco-pharmacy, are presented in this article. The classification of drugs according to their eco-pharmacological profile have been presented for the first time. The criteria by which drugs can be considered as eco-pharmacological or eco-pharmacologically hazardous have been defined. The reference points, according to which the patient’s treatment can be characterized as eco-pharmacotherapy, are identified. The issue of safe disposal of unsuitable drugs has been updated. A new interdisciplinary direction that combines pharmacy, ecology and chemistry, namely eco-pharmacy, has been suggested. Optimization and personification of therapy with the prescription of primarily eco-pharmacological drugs will allow to evolve into the level of eco-pharmacotherapy and to reduce the amounts of prescriptions for eco-pharmacologically hazardous drugs. One of the most important issues of eco-pharmacy at the present stage is the improvement of disposal of unsuitable drugs.